2004
DOI: 10.1111/j.1467-7687.2005.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive development of deaf children: lessons from the appearance–reality and false belief tasks

Abstract: 'Theory of mind' development is now an important research field in deaf studies. Past research with the classic false belief task has consistently reported a delay in theory of mind development in deaf children born of hearing parents, while performance of second-generation deaf children is more problematic with some contradictory results. The present paper is aimed at testing the metacognitive abilities of deaf children on two tasks: the appearance-reality paradigm designed by Flavell, Flavell and Green (1983… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 39 publications
1
33
2
2
Order By: Relevance
“…In the early stages of social cognitive development these children, even with early cochlear implants might experience a different quality of conversation and interaction during the period their parents adapt to their infant's deafness. Many previous studies have reported that deaf children aged 4 years and above and from hearing families who do not use sign language effectively, display a protracted delay in Conversational input to deaf children 4 Theory of Mind (ToM) reasoning on explicit tests (Courtin & Melot, 2005;Figueras-Costa & Harris, 2001;Meristo, Hjelmquist, Surian & Siegal, in press;Morgan & Kegl, 2006;Pyers & Senghas, 2009;Peterson & Siegal, 1995, 1999Schick, de Villiers, de Villiers, & Hoffmeister, 2007;Woolfe, Want, & Siegal, 2002). In elicited response methodologies the child is explicitly required to respond overtly to a question or prompt about the mental states of another person in the test.…”
Section: Conversational Input To Deaf Childrenmentioning
confidence: 99%
“…In the early stages of social cognitive development these children, even with early cochlear implants might experience a different quality of conversation and interaction during the period their parents adapt to their infant's deafness. Many previous studies have reported that deaf children aged 4 years and above and from hearing families who do not use sign language effectively, display a protracted delay in Conversational input to deaf children 4 Theory of Mind (ToM) reasoning on explicit tests (Courtin & Melot, 2005;Figueras-Costa & Harris, 2001;Meristo, Hjelmquist, Surian & Siegal, in press;Morgan & Kegl, 2006;Pyers & Senghas, 2009;Peterson & Siegal, 1995, 1999Schick, de Villiers, de Villiers, & Hoffmeister, 2007;Woolfe, Want, & Siegal, 2002). In elicited response methodologies the child is explicitly required to respond overtly to a question or prompt about the mental states of another person in the test.…”
Section: Conversational Input To Deaf Childrenmentioning
confidence: 99%
“…Previous studies focused on signing deaf children of deaf parents from middle-high SES. These studies found that the children were not delayed in their TOM development, due to rich linguistic and social interactions they experienced (Courtin, 2000;Courtin & Melot, 2005;Schick, De-Villiers, De-Villiers & Hoffmeister, 2007). However, studies on hearing children of low SES pointed to a significant discrepancy between them and children whose SES is higher on a variety of linguistic and cognitive abilities, among them ToM (Curenton & Craig, 2011;Cutting & Dunn, 1999;Holmes et al, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to deaf children with hearing parents who have difficulty attributing mental states to people, deaf children whose parents are also deaf and who communicate with them using sign language from infancy do not exhibit difficulties in ToM development (Courtin, 2000;Courtin & Melot, 2005;De Villers, 2006;Schick et al, 2007). The intact ToM among these children can be attributed first and foremost to their early and normal exposure to mental states through their natural and fertile communication in sign language, which is their mother tongue (Meir, 2007).…”
Section: Development Of Tom Among Deaf Childrenmentioning
confidence: 99%
“…Our results confirm the hypothesis described in the "Introduction": Deaf children in a bilingual curriculum outperformed deaf children attending the school with a TA in all tasks and the performance of hearing was in between those of the two deaf groups. Earlier studies reported important differences between native-signing children (those who have had access from birth to a sign language used by deaf family members) and late-signing deaf children (those who have hearing parents and have gained access to a sign language later in school; Courtin & Melot, 2005;Jackson, 2001;Peterson & Siegal, 1999;Schick et al, 2007;Woolfe et al, 2002). In our sample, all deaf children were signing at the age of assessment, but it was not always the case that children with deaf parents had learned sign language early in life or that deaf children of hearing parents had learned sign language late in life, as we explained in detail in the "Method" section (see Table 1 reporting hearing status of parents, first exposure to LIS and use of LIS at home).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The picture became more complex when studies conducted with deaf children from deaf families showed that these children, who acquire their sign language from an early age (often referred to as "native signers") do not appear to be delayed in their ToM development (Courtin & Melot, 2005;Jackson, 2001;Peterson & Siegal, 1999Woolfe, Want, & Siegal, 2002).…”
Section: Assessing Mentalizing (Theory Of Mind) Skillsmentioning
confidence: 99%